Systems analysis of transcriptional data provides insights into muscle's biological response to botulinum toxin. Issue 5 (17th March 2014) - Mukund, Kavitha; Mathewson, Margie; Minamoto, Viviane; Ward, Samuel R.; Subramaniam, Shankar; Lieber, Richard L.
ABSTRACT Introduction: This study provides global transcriptomic profiling and analysis of botulinum toxin A (BoNT‐A)–treated muscle over a 1‐year period. Methods: Microarray analysis was performed on rat tibialis anterior muscles from 4 groups (n = 4/group) at 1, 4, 12, and 52 weeks after BoNT‐A injection compared with saline‐injected rats at 12 weeks. Results: Dramatic transcriptional adaptation occurred at 1 week with a paradoxical increase in expression of slow and immature isoforms, activation of genes in competing pathways of repair and atrophy, impaired mitochondrial biogenesis, and increased metal ion imbalance. Adaptations of the basal lamina and fibrillar extracellular matrix (ECM) occurred by 4 weeks. The muscle transcriptome returned to its unperturbed state 12 weeks after injection. Conclusions: Acute transcriptional adaptations resemble denervated muscle with some subtle differences, but resolved more quickly compared with denervation. Overall, gene expression across time correlates with the generally accepted BoNT‐A time course and suggests that the direct action of BoNT‐A in skeletal muscle is relatively rapid. Muscle Nerve50: 744–758, 2014